RANCANG BANGUN INSTALASI AKUAPONIK PADA POKDAKAN “BANGKIT MENUJU SUKSES” DI KELURAHAN ANTASAN KECIL TIMUR KOTA BANJARMASIN - Rahmawati, Linda; Iswahyudi, Herry; Wahyudi, Ikhsan; Lukmana, Mila; Abdillah, Muhammad Helmy; Indriani, Indriani; Indayaty, Amirilia; Prasetyo, Nur Hidayat Eko; Nasrullah, Muhammad; Julianto, Tri (Universitas Mataram, 2025)
Limited land is the main challenge in aquaculture activities at the Bangkit Menuju Sukses fish farming group (Pokdakan) in Antasan Kecil Timur Village, Banjarmasin City. So far, many Pokdakans have only been able to utilize limited space for fish farming, at the same time program plans to grow vegetables are hampered by the lack of available land, the lack of farming skills, and the absence of training are obstacles in product development. The aquaponics system is an innovative solution that integrates fish and plant farming into a single integrated ecosystem. The purpose of this activity is to design an aquaponic system in Pokdakan Bangkit Menuju Sukses, to enhance skills in cultivating both fish and plants. The method used in this activity is the delivery of material, the practice of making installations, and filling out questionnaires by answering pre-test, post-test, and affective questionnaires. The results obtained in this activity are the increased understanding of residents about aquaponic technology installed aquaponic system installations. Participants responded positively to the activity and hoped that community service activities could be sustainable.